(untitled) (Journal of the College of Basic Education, 2022)
The peoples of the world are proud and proud of their cultural heritage, and this feeling increases whenever it is discovered. Man believes that the civilization to which he belongs has depth and contents of values. Perhaps myths are one of the The important topics embodied by the artists in their artwork. The research dealt with the legend (One Thousand and One Nights). That subject was embodied by the sculptor Muhammad Ghani Hikmat in his many monumental works, and the researcher wonders On the expressive potential of the artist and his ability to include in his monumental works themes that express their contents.